Pengaruh Modal Kerja dan Penjualan terhadap Laba Bersih Perusahaan Food and Beverages yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Agustina Agustina; Youdhi Prayogo; Faturahman Faturahman (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research aims to examine working capital and sales both partially and simultaneously on net profit in Food and Beverages companies listed on the IDX in 2020-2022. Working capital and sales are used as independent variables, while net profit is used as the dependent variable. This research uses a quantitative type of research. The data used is secondary data. Statistical data analysis techniques using SPSS (Statistical Package For Social Sciences) 22 for Windows program tools, namely multiple linear regression analysis. The results of this research show that partially working capital has a significant effect and partially sales does not have a significant effect on net profit. And working capital and sales simultaneously influence net profit.